DPSK modulated wakeup mechanism for point-to-point networks with partial network support - Seyler, Jan; Rahimov, Shurat; Streichert, Thilo; Glaß, Michael; Teich, Jürgen (Proceedings of the 9th IEEE International Symposium on Industrial Embedded Systems (SIES), 2014)
The automotive community introduced Ethernet as a packet-switched point-to-point network. Possible fields of application are telematics, advanced driving assistance and a backbone. Currently, CAN, FlexRay and MOST are used to interconnect these applications. With Ethernet the bandwidth is rising but the networking requirements are still the same as for existing field buses. Consumer Ethernet does not provide a wakeup mechanism that is sufficient for automotive systems. As a solution, this paper introduces a novel DPSK based physical-layer mechanism which uses digital signals to identify partial networks and has an overall wakeup latency of less than 5 ms which is a reduction of 75 % for a five-hop network to the current state-of-the-art technology for automotive point-to-point networks. © 2014 IEEE.